Pelatihan Penggunaan Media Pembelajaran Dakota untuk Meningkatkan Minat Belajar Siswa pada Materi KPK dan FPB - Muh. Rais; Nurjannah; Andi Baso Kaswar (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Mathematics is a part of science and takes an important part in the life and improvement of science, information and innovation. The purpose of this service is to explain the use of Dakota learning media (Mathematics Dakon) to attract students' interest in learning and also have fun in learning mathematics, especially on the KPK (Least Alliance Multiples) and FPB (Largest Fellowship Factor) materials. This community service was carried out at SD Negeri 83 Aruhu, Lamatti Riaja Village, Bulupoddo District. From February 23, 2022 to February 26, 2022, Dakota game-based learning activities are carried out in the classroom, with a total of 38 elementary school students, followed by students in grades IV, V and VI. There are three stages, namely the preparation, implementation and evaluation stages. that 86% of students at SD Negeri 83 Aruhu understand the subject matter taught through dakon games and 94% of students enjoy learning mathematics the learning process using mathematics dakon goes smoothly and students are interested in using mathematics dakon media.